SUBALTERN IDENTITY AND FILM CODE IN CINEMA FROM THE SOUTH OF INDIA - Kamei, Machunwangliu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In 2023, the Indian film industry's market size surpassed 197 billion rupees, showcasing a significant recovery trajectory following the COVID-19 pandemic (Statista, 2024), with South Indian cinema in Tamil, Malayalam, Kannada, and Telugu languages gaining notable popularity. South Indian cinema has historically been interwoven with regional politics, with films reflecting social and political tensions through ideologically charged narratives. These cinematic narratives frequently construct heuristic, hyperreal imagery, drawing upon real-life references yet developing unique symbolic characteristics on screen. Through a critical examination, this study reveals how the intertwined themes of endogamy, identity politics, hegemony, and exclusivism are embedded within the philosophical foundation of these films, reflecting or refracting the societal dynamics they aim to represent or critique.